PENGARUH MODEL PEMBELAJARAN EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR SIMULASI DIGITAL MATAKULIAH KELAS X TEKNIK KOMPUTER DAN JARINGAN (TKJ) - Muhammad Hakiki; Arisman Sabir; Rani Kartika; M Iqbal Al-ihsan (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Learning outcomes are influenced by several factors, one of which ia a method of learning. This study alms to determine the effect of learning model Explicit Instruction on learning outcomes digital simulation class X computer engineering and network in SMKN 1 Bungo second semester of academic year 2020/2021. This research is a quantitative research with this type of Experimental research. This research conducted in SMKN 1 Bungo in March to April. Sample data collection is done by using the technique Random Sampling, where the population in this study student grade X TKJ 1 totaling 31 people and 31 people TKJ 2 as a Experimentalt class and class TKJ 1 as the control class. Based on the results of the study, the average student learning outcomes of experimental in class (81.81), while the control class (72.90). From the analysis of the test data to obtain Normal data and Homogeneous. Data analysis techniques used in this research is the t-test, The results ofthe testat significance level α of 0.05 (95% confidence level) obtained tvalue=5.623 and ttable=2.000 thus tvalue > ttable (5.623 >2.000), then H0 is rejected and Ha is accepted. Thus, the conelusion that there is a significant and positive affect on learning model explicit instruction learning model influence on the results of class x digital simulation study computer engineering and network in SMK N 1 Bungo.